Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.ijid.2020.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial artemisinin-based combination therapies (ACT) and COVID-19 in Africa: In vitro inhibition of SARS-CoV-2 replication by mefloquine-artesunate

Abstract: Objectives At the end of November 2019, a novel coronavirus responsible for respiratory tract infections (COVID-19) emerged in China. Despite drastic containment measures, this virus, known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), spread in Asia and Europe. The pandemic is ongoing with a particular hotspot in Southern Europe and America; many studies predicted a similar epidemic in Africa, as is currently seen in Europe and the United States of America. However, reported da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 28 publications
(29 reference statements)
2
78
0
2
Order By: Relevance
“…However, some antimalarial drugs have been documented as future drugs for the treatment of COVID 19. Verifiable treatment with remodel antimalarial drugs such as chloroquine, hydroxychloroquine, azithromycin, pyronaridine and Artemisinin-based combination therapy (ACT) is going on [19].…”
Section: Antimalarial Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some antimalarial drugs have been documented as future drugs for the treatment of COVID 19. Verifiable treatment with remodel antimalarial drugs such as chloroquine, hydroxychloroquine, azithromycin, pyronaridine and Artemisinin-based combination therapy (ACT) is going on [19].…”
Section: Antimalarial Drugsmentioning
confidence: 99%
“…In order to eliminate the evolution of resistance acquired by malaria parasites, the need to develop newer drug regimen [22]. A plant-based antimalarial drug was isolated from the Chinese plant Artemisia annua in seventies, World Health Organization recommended the use of artemisin in based combination therapy (ACT) as first line therapy for the treatment of uncomplicated malaria to increase the goal of treatment and prevent emergence of resistance to therapy [19,20,22]. Artemisinin derivatives have very short half-lives, thus using them as monotherapy requires doses over a period of 7 days.…”
Section: Artemisinin Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike chloroquine that was withdrawn in the late 1990s due to growing resistance to it by the plasmodium pathogen [9][10][11][12], most (n = 65/67, 97%) malaria endemic countries including 41 Africa countries adopted artemisinin combine terapy (ACT) as their first line of treatment for uncomplicated malaria in 2000 [13]. One study has demonstrated in vitro the clinical effectiveness of artemisinin in the treatment of COVID-19 [14].…”
mentioning
confidence: 99%
“…Desconocemos la influencia de SARS-CoV-2 en la evolución de la malaria grave, así como la posible influencia del tratamiento antipalúdico con derivado de la artemisinina que recibió el paciente. Gendrot et al 11 , tras comprobar actividad in vitro , proponen la utilidad de las combinaciones antimaláricas con alta concentración en parénquima pulmonar como terapias prospectivas en COVID-19 11 . Hipótesis que precisará de futuros estudios de investigación que aborden esta cuestión dada la ausente casuística comunicada de coinfección SARS-CoV-2 y Plasmodium falciparum en la literatura .…”
unclassified